A Retrospective Study: Bartholin Cyst and Abscess - Tjokorde Istri Nindya Vaniary; Sunarko Martodihardjo (Faculty of Medicine, Universitas Airlangga, 2017)
Background: Bartholin cyst is an enlargement of the duct gland as a result of some blockade. Infected Bartholin cyst can develop into an abscess. The diseases are common in reproductive women but the ideal treatment for this disease remains controversial. Purpose: To evaluate the management of Bartholin cyst and abscess in new patients according to diagnosis approach by anamnesis and physical examination. Methods: This study is a retrospective descriptive study. The data were drawn from medical records of new patients Bartholin cysts and abscesses in the Division of Sexually Transmitted Infections in Outpatient Clinic of Dermatovenereology Dr. Soetomo General Hospital during 2012-2014. Results: During 2012-2014, there are 46 patients with Bartholin cyst and 25 with Bartholin abscess. Visit times tend evenly throughout the year without a distinctive pattern. Most patients were in the age group 25-44 and married. Based on the history, 65.2% and 80.0% of patients with Bartholin cyst and abscess complained for a lump. From the physical examination, 39.1% and 44.0% of patients with Bartholin cyst and abscess had a lump size of 1-3 cms, most have a flat surface properties, a rubbery consistency, and obtained inflammatory signs. Gram and a wet mount examination performed at 84.8% and 72.0% of patients with Bartholin cyst and abscess, and showed normal results. Most treatment given to the patients with Bartholin cyst were antibiotics (60.9%) and patients with Bartholin abscess were given more than one treatment and most treatments given were antibiotics (64.0%) and non-steroidal anti-inflammatory drugs (72%). Conclusion: The diagnosis approach of Bartholin cyst and abscess was obtained by anamnesis, physical examination, and additional examination. Most of Bartholin cyst and abscess treated with antibiotics and NSAID, most of surgical treatment is marsupialization.